LOW TEMPERATURE SOL-GEL SYNTHESIS OF TIN OXIDE NANOPARTICLES FOR PHOTOELECTROCHEMICAL SOLAR CELL APPLICATION - S. BHANDE, SAMBHAJI (Innovare Journal of Sciences, 2020)
A renewable energy has been always a topic of interest for researchers. The aevances in solar cells from first generation to third generation solar cells have seen many materials. The low cost gratzel cells have made an impact on the solar cell manufacturing although the low efficiency as compared to silicon solar cells the low cost manufacturing and abondant material availability for large production makes it a potential candidate.The tin chloride precursor initiated sol-gel chemical method for synthesizing tin oxide (SnO2) nanoparticles electrode is envisaged in dye-sensitized solar cells. Three steps; synthesis of nanoparticles, formation of paste using suitable surfactants and film development using doctor-blade method, are adopted for obtaining SnO2 electrode. The films of SnO2 nanoparticles formed onto glass and indium-tin-oxide substrates are annealed at 450 °C for 3 h. Influence of indium-tin-oxide on the structural elucidation, morphological evaluation, grain size confirmation and Raman shift analysis of the SnO2 nanoparticles is eliminated by considering glass as the depositing substrate. Enhanced light absorbance at 500 nm due to the N719 dye molecules adsorption compared to pristine SnO2 electrode has showed 1.62% solar-to-electrical conversion efficiency.